Khrōngkān Lūang Phāk Nư̄a = The Royal Northern Project. ([Bangkok?] : [publisher not identified], 1980)
Description of agricultural, economic, and social development project under royal patronage in northern Thailand.
Thai and English.
Keywords: Agriculture and state -- Thailand, Northern; Agriculture and state; Economic policy; Social policy; Thailand, Northern -- Economic policy; Thailand, Northern -- Social policy; Northern Thailand